High-accuracy infra-red thermography method using reflective marker arrays - Kirollos, B; Povey, T (Institute of Physics, 2017)
In this paper, we describe a new method for high-accuracy infra-red (IR) thermography measurements in situations with significant spatial variation in reflected radiation from the surroundings, or significant spatial variation in surface emissivity due to viewing angle non-uniformity across the field of view. The method employs a reflective marker array (RMA) on the target surface - typically, high emissivity circular dots - and an integrated image analysis algorithm designed to require minimal human input. The new technique has two particular advantages which make it suited to high-accuracy measurements in demanding environments: (i) it allows the reflected radiation component to be calculated directly, in situ, and as a function of position, overcoming a key problem in measurement environments with non-uniform and unsteady stray radiation from the surroundings; (ii) using image analysis of the marker array (via apparent aspect ratio of the circular reflective markers), the local viewing angle of the target surface can be estimated, allowing corrections for angular variation of local emissivity to be performed without prior knowledge of the geometry. A third advantage of the technique is that allows for simple focus-stacking algorithms due to increased image entropy. The reflective marker array method is demonstrated for an isothermal, hemispherical object exposed to an external IR source arranged to give a significant non-uniform reflected radiation term. This is an example of a challenging environment, both because of the significant non-uniform reflected radiation term, and also the significant variation in target emissivity due to surface angle variation. We demonstrate that the new RMA IR technique leads to significantly lower error in evaluated surface temperature than conventional IR techniques. The method is applicable to any complex radiative environment.